2019
DOI: 10.12659/msm.917537
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of a Radiation-Induced Brain Injury Model and Preliminary Study on the Effect of Human Recombinant Endostatin in Treating Radiation-Induced Brain Injury

Abstract: BackgroundThe aim of this study was to construct a radiation-induced brain injury (RBI) model and assess the effects of human recombinant endostatin in the treatment of RBI.Material/MethodsIn this study, the RBI model was used. Real-time quantitative polymerase chain reaction, immunohistochemistry, hematoxylin and eosin staining were conducted to detect the mRNA and protein expression of vascular endothelial growth factor (VEGF) and assess the effects of human recombinant endostatin in the treatment of RBI.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Consequently, pathological levels of VEGF inevitably result in vasogenic cerebral edema (44), which was consistent with our data in the anlotinib treated groups. Also, Ma et al (45) showed that thrombosis could be observed from 3 to 7 days after irradiation, while thrombus recanalization is first achieved at 14 days. In combination with the histological results, they believed that the sharp increase in BWC at 14 days after irradiation not only results from the over-expression of VEGF, but also with thrombus recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, pathological levels of VEGF inevitably result in vasogenic cerebral edema (44), which was consistent with our data in the anlotinib treated groups. Also, Ma et al (45) showed that thrombosis could be observed from 3 to 7 days after irradiation, while thrombus recanalization is first achieved at 14 days. In combination with the histological results, they believed that the sharp increase in BWC at 14 days after irradiation not only results from the over-expression of VEGF, but also with thrombus recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…This response was inhibited by GABAa antagonist bicuculline [29]. Therefore, declining the GABAergic neurotransmission in the hypothalamus could be contributing to the decreased appetite and weight loss observed after WBI [11,[30][31][32]. Hypothalamic GABA neurons are also known to regulate several physiological and behavioral responses associated with anxiety and stress.…”
Section: Discussionmentioning
confidence: 99%
“…This response was inhibited by GABAa antagonist bicuculline [34]. Therefore, declining the GABAergic neurotransmission in the hypothalamus could be contributing to the decreased appetite and weight loss observed after WBI [11,[35][36][37]. Hypothalamic GABA neurons are also known to regulate several physiological and behavioral responses associated with anxiety and stress.…”
Section: Discussionmentioning
confidence: 99%